Penerapan Metode Trend Moment untuk Prediksi Penjualan Kebab : Penerapan Metode Trend Moment untuk Prediksi Penjualan Kebab: Studi Kasus Kebab Turki Zahara - FEBRIANI, WIDYA (Universitas Siber Indonesia, 2025)
The food business presents a significant profit potential due to high public interest in food. Food business owners aim to maximize profits and survive competition, one way being through product sales forecasting. Sales prediction is crucial for optimizing profits and minimizing losses from the accumulation of raw material inventory. This research aims to predict the sales volume of Kebab Turki Zahara for the upcoming month using the Trend Moment Method. The test results indicate that this method is optimal for sales prediction, thereby helping to optimize sales and the management of kebab raw material stock.